A sound-absorbing and heat-insulating collagen fiber composite material. Issue 1 (January 2023) - Hui Chen, Jiaxing Zhang; Shan, Zhihua
Using methacrylic acid (MAA) and methyl methacrylate (MMA) as core monomers and polystyrene as the shell layer, polymer hollow microspheres (PHM) with good stability were prepared by using an alkali osmotic swelling method followed by spray drying. The average size of the PHM was approximately 875 nm. As a filling cross-linking agent, the PHM were added to a skin collagen material to disperse and fix, and a "polymer hollow microsphere composite collagen fiber" (PHCC) material was obtained. The results show that the PHM improve the mechanical strength, thermal stability and water resistance of the skin collagen material. The PHCC material has a low thermal conductivity (0.035 W/(K·m)) and excellent sound insulation performance and retains the soft and delicate touch of leather, which has application value in high-grade decorative materials and functional leather. This provides a new approach for developing flexible sound-absorbing thermal insulation materials.